2020
DOI: 10.1371/journal.pone.0239460
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital use of a modified HEART Pathway and point-of-care troponin to predict cardiovascular events

Abstract: The HEART Pathway is a validated risk stratification protocol for Emergency Department patients with chest pain that has yet to be tested in the prehospital setting. This study seeks to test the performance of a prehospital modified HEART Pathway (PMHP). A prospective cohort study of adults with chest pain without ST-segment elevation myocardial infarction was conducted at three EMS agencies between 12/2016-1/2018. To complete a PMHP assessment, paramedics drew blood, measured point-of-care (POC) troponin (i-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
(37 reference statements)
0
15
0
Order By: Relevance
“…Currently, several studies, demonstrated that in patients with suspected NSTE-ACS pre-hospital risk assessment is feasible, and that outcome is comparable with risk assessments performed in the hospital. 30 , 31 Although previous studies showed promising results, structured pre-hospital risk assessment is not yet implemented in routine daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies, demonstrated that in patients with suspected NSTE-ACS pre-hospital risk assessment is feasible, and that outcome is comparable with risk assessments performed in the hospital. 30 , 31 Although previous studies showed promising results, structured pre-hospital risk assessment is not yet implemented in routine daily practice.…”
Section: Discussionmentioning
confidence: 99%
“…com/EJEM/A333). The high risk of bias was found with respect to flow and timing, due to considering patients with incomplete follow-up as free of MACE [10,41]. We found all studies at low concern regarding applicability.…”
Section: Description Of Included Studiesmentioning
confidence: 77%
“…An example of such scores are the preHEART and the modi ed HEART pathway which use the patients' history, ECG, risk factors and a Point-of-Care (POC) Troponin. (15,16) These scores provide paramedics with the opportunity to make a strati cation of likelihood for patients with undifferentiated chest pain for having a NSTEMI. The likelihood ratio of combined risk scores for risk strati cation in suspected NSTEMI patients are currently better then standalone history, ECG and, POC-Troponin alone.…”
Section: Pre-hospital Triagementioning
confidence: 99%